[Memorandum on Australian constitutions] - Herbert of Lea, Sidney Herbert, Baron, 1810-1861. (1854)
Memorandum on Australian consitutions in which their status under the Australian Colonies Government Act 1850 is described together with recommendations for establishing responsible government in each of the three colonies.
Manuscript reference no.: NLA MS 1302.
Keywords: Australia; New South Wales -- Politics and government; Victoria -- Politics and government; Tasmania -- Politics and government